The Effect of Starch Concentration on the Characteristics of Modified Purple Yam Starch Using the Precipitation Method: Pati uwi ungu modifikasi - Parera, Yogi; ulyarti, ulyarti; Gusriani, Ika (Jurnal Bio-Geo Material Dan Energi, 2021)
Purple yam starch-based edible film experienced high water vapor transmission rate. The use of composite starch using addition of modified starch of smaller size particles may decrease the rate. This study aimed to obtain starch concentrations that produced smallest size of modified starch, to produce composite starch for edible films and to determine the characteristics of edible films made out of native starch and edible films from composite starch (mixture of native starch and modified starch with the smallest size). This research was conducted in 2 stages: modification of purple yam starch by precipitation method and production of edible films from native starch and composite starch. This study was designed to produce modified starch using 5 levels of starch concentration (0,2%, 0,4%, 0,6%, 0,8%, and 1%) and 2 repetitions. The results showed that the treatment of 0,8% starch concentration produced the smallest particle size of starch (3,211 x 10,340 µm) up to (20,876 x 25,437 µm) with starch yield of 76,25%. Edible films made out composite starch have different characteristics than native starch alone. Edible films from composite starch produced higher thickness values ​​of 0.161 ± 0.007 mm, lower solubility 32,080 ± 4,671%, lower transparency of 10.644 ± 0.357% / mm and lower water vapor transmission rate (WVTR) of 24,701 ± 7,05 g / m2. hour and higher compressive strength 356,87 ± 7,38 gF than native starch edible films.